Investigating Islamic Religious Education learning in Public Higher Education: epistemological, ontogenic, and didactic barriers - Sanusi, Anwar; Abdulkhaleq Al-Rawafi; Arum Gati Ningsih (Indonesian Journal of Islamic Religious Education, 2024)
This study aims to identify epistemological, ontogenic, and didactic barriers to Islamic Religious Education learning in public higher education. A qualitative approach with a case study design was used to collect data through in-depth interviews, classroom observations, and document analysis. The findings indicate that students' difficulties connecting Islamic teachings with modern sciences, such as economics and technology, arise from epistemological barriers. As many as 75% of students complained about the lack of relevance of Islamic Religious Education materials to their fields of study. Ontogenic barriers are related to students' mental unpreparedness, including anxiety, lack of self-confidence, and inability to participate actively in learning. Unstable psychological conditions, such as stress and time management disorders, exacerbate this problem. On the other hand, didactic barriers were identified in using one-way lecture teaching methods that reduce student engagement and the lack of variation in learning strategies that connect theory to contemporary issues. This study suggests improvements in teaching methods, emphasizing interactive and problem-based approaches and increasing student involvement in discussions to deepen a comprehensive understanding of religion. In addition, strengthening practical learning, such as teaching Tajweed and applying religious teachings in a modern context, is expected to overcome these barriers